An Optimized Image Encryption Technique for Multikey conservative chaotic system (International Journal of Engineering and Computer Science, 2015)
In             recent        years         of             wireless     access communication,     the     internet     and     other  computer communication technologies are radically changing the ways of communication and information exchanging source. However, along with speed, efficiency and cost-saving benefits of the digital revolution, there exists a new challenge for the security and privacy of communication of information. Hence cryptographic algorithms are efficient tool for encryption. In this paper a new color image encryption algorithm is proposed by combining Lorentz and Rossler attractor with multi-key concept for conservative chaotic system. Also, the pixel values of the plain image are modified randomly using confusion and diffusion process to strengthen the image security. The resultant encrypted image is compared with various results obtained using single and multi key algorithms. The proposed algorithms is also analyzed under different critical attacks and the results show that the proposed system has a better efficiency, image confidentiality, high encryption and decryption speed.